Pemodelan Peningkatan Akurasi Estimasi Biaya Dengan Metode Structural Equation Modeling-Partial Least Square Pada Proyek Jalan Provinsi Kalimantan Tengah - Christian, Yanda; Harimurti, Harimurti; Wijatmiko, Indradi (Rekayasa Sipil, 2017)
Acceleration of national development increases the number of construction projects in Indonesia, including road projects. The contractor as the service provider in the implementation of the construction work shall have a detailed implementation schedule and project cost budget plan so that the construction work shall not be subject to delays and cost overrun. The main thing that can cause cost overrun is the error in cost estimation. In this study discusses the modeling of increasing the accuracy of cost estimation as well as the development of factors that can improve the accuracy of cost estimation. Validation of research variables was done to experts using Analytical Hierarchy Process (AHP) method and modeling using Structural Equation ModelingPartial Least Square (SEM-PLS) method to project contractor of Public Works Department of Central Kalimantan Province and National Road Implementation Center XI Unit Work of Central Kalimantan with contract value of project worth 20 Billion to 50 Billion Rupiah Year 2016. The result of variable validation shows the competence variable of estimator, survey, availability of information, calculation of cost estimation and internal company is variable which influence estimation The obtained modeling equation is AEB = 0,129 KE + 0.466 S + 0,191 KI + 0,153 PEB + 0,069 IP + 0,181 Î¶. The development of cost estimation is done by improving each influential indicator in each variable and applying development strategies to increase the estimated cost estimation based on SWOT analysis.Â